Diagnostic accuracy of non-contrast abdominal CT scans performed as follow-up for patients with an established cancer diagnosis: a retrospective study. (4th March 2018) - Semaan, Hassan; Bazerbashi, Mohamad F.; Siesel, Geoffrey; Aldinger, Paul; Obri, Tawfik
Abstract: Objectives: To determine the accuracy and non-detection rate of cancer related findings (CRFs) on follow-up non-contrast-enhanced CT (NECT) versus contrast-enhanced CT (CECT) images of the abdomen in patients with a known cancer diagnosis. Methods: A retrospective review of 352 consecutive CTs of the abdomen performed with and without IV contrast between March 2010 and October 2014 for follow-up of cancer was included. Two radiologists independently assessed the NECT portions of the studies. The reader was provided the primary cancer diagnosis and access to the most recent prior NECT study. The accuracy and non-detection rates were determined by comparing our results to the archived reports as a gold standard. Results: A total of 383 CRFs were found in the archived reports of the 352 abdominal CTs. The average non-detection rate for the NECTs compared to the CECTs was 3.0% (11.5/383) with an accuracy of 97.0% (371.5/383) in identifying CRFs. The most common findings missed were vascular thrombosis with a non-detection rate of 100%. The accuracy for non-vascular CRFs was 99.1%. Conclusion: Follow-up NECT abdomen studies are highly accurate in the detection of CRFs in patients with an established cancer diagnosis, except in cases where vascular involvement is suspected.